Peias e espartilhos: sátira popular à moda francesa na Primeira República - Marques, Francisco Claudio Alves [UNESP]; Silva, Esequiel Gomes da [UNESP] (My University, 2014)
In the first decades of the Republic, the streets of the main Brazilian capital cities, especially of Rio de Janeiro and Recife, recently urbanized based on the Haussmanian Paris and smiled upon by the fever of cosmopolitanism that invested Europe, women had been used as runways where they could exhibit her imitated or imported models, especially in Paris. The iconography of the time and the advertisements conveyed by magazines and illustrated periodicals, such as the Almanach de Pernambuco and the magazine Kosmos, for instance, form the testimonies of the massive presence of the French in Rio and Recife, owners of stores and maisons, interested in fulfill the demands of the republican public. In spite of the Strong adherence of the Brazilians to the sociability models to the imported from Europe, the less-favored classes, through the popular literature, showed some resistance to these changes in the habits and clothing, especially in the Northeast, where traces of the Catholic and patriarchal moral and mentality were still alive.

Nas primeiras décadas da República, as ruas das principais capitais brasileiras, sobretudo do Rio de Janeiro e do Recife, reurbanizadas nos moldes da Paris haussmanniana e bafejadas pela febre de cosmopolitismo que investia a Europa, ofereciam-se às mulheres como passarelas onde podiam exibir seus modelos imitados ou importados, principalmente de Paris. A iconografia e os anúncios veiculados pelas revistas e periódicos ilustrados da época, como o Almanach de Pernambuco e a revista Kosmos, por exemplo, configuram-se testemunhos da maciça presença de franceses no Rio e em Recife, proprietários de lojas e maisons interessados em atender às exigências do público republicano. Apesar da forte adesão dos brasileiros aos modelos de sociabilidade importados da Europa, as classes menos favorecida, por meio da literatura popular, manifestava certa resistência a essas mudanças nos costumes e na indumentária, principalmente no Nordeste, onde ainda reinava resquícios da mentalidade e da moral católica e patriarcal.
Clogs and corsets: popular satire on the french way in the First Republic
Keywords: Sátira; Literatura de Cordel; Leandro Gomes de Barros; Moda Francesa; Primeira República; Crítica social; cultura popular; Literatura de cordel; Sátira